ANALISIS TINDAK TUTUR ILOKUSI ASERTIF DALAM DAFTAR PUTAR VIDEO DARI CHANNEL PRODI SEJARAH UNAIR YANG BERJUDUL MATERI SEJARAH: Analysis of Assertive Illocutionary Acts in A Video Playlist From UNAIR History Study Program Channel Entitled Historical Material - Maulana Saiful Rizal; Faizal Adi Pradipta; Asep Purwo Yudi Utomo (Kantor Bahasa Provinsi Maluku, 2023)
Abstract An illocutionary speech act is the act of doing something, which talks about the intention, function or related speech power. The purpose of this study is to analyze and explain the types of assertive speech acts in the